Market Day: Sharpening Children's Entrepreneurial Spirit from an Early Childhood in a Fun Way - Iftitah, Selfi Lailiyatul (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2024)
Market day is one of the strategies to develop entrepreneurial character in early childhood. This study aims to determine how the Market Day Program develops entrepreneurial character in early childhood. This study uses a literature study method by analyzing literature and relevant sources that discuss the Market Day Program to develop entrepreneurial spirit in early childhood. The results of the literature study indicate that the market day program develops entrepreneurial character in early childhood, including creativity, problem-solving skills, social skills, and a sense of responsibility. The market day program provides children with direct experience in planning, producing, and selling products, which supports the development of their entrepreneurial skills. Â Market day adalah salah satu strategi untuk mengembangkan karakter jiwa kewirausahaan pada anak usia dini.. Penelitian ini bertujuan untuk mengetahui bagaimana Program Market Day mengembangkan jiwa kewirausahaan anak usia dini Â Penelitian ini menggunakan metode studi pustaka dengan menganalisis literatur dan sumber-sumber relevan yang membahas Program Market Day untuk mengembangkan jiwa kewirausahaan anak usia dini. Hasil studi pustaka menunjukkan bahwa program market day mengembangkan karakter jiwa kewirausahaan anak usia dini, diantaranya adalah kreativitas, kemampuan memecahkan masalah, keterampilan sosial, dan rasa tanggung jawab. Program market day memberikan pengalaman langsung kepada anak dalam merencanakan, memproduksi, dan menjual produk, yang mendukung pengembangan keterampilan kewirausahaan mereka.